2008
DOI: 10.2186/prp.7.40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Palatal Plate on Tongue Pressure during Swallowing

Abstract: Covering the palate with dentures can disrupt the timing of swallowing. To determine the cause of this phenomenon, we investigated whether covering the palate with a denture base altered tongue pressure. The results suggest that use of a denture base has little effect on tongue pressure during swallowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Kodaira et al [32] placed experimental palatal plates on the tongues of adults with a mean age of 25 years and measured changes in MTP against the palate with and without the palatal plate. They found that the palatal plate had no effect on MTP, similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Kodaira et al [32] placed experimental palatal plates on the tongues of adults with a mean age of 25 years and measured changes in MTP against the palate with and without the palatal plate. They found that the palatal plate had no effect on MTP, similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the insertion of a palatal plate does not change tongue pressure [15], and that when the thickness of a palatal plate does not exceed 1.5 mm, tongue movement is not influenced during swallowing [16]. These findings suggest that the insertion of the palatal plates did not influence the ease of swallowing because the thickness of the palatal plate did not exceed 1.5 mm.…”
Section: Discussionmentioning
confidence: 74%
“…Tongue strength was found to be the predictive factor which decreased oral residue and increased pharyngeal residue in the case of swallow once after 30 chewing actions of bread, which suggested the importance of multiple swallow in the elderly with poor masticatory ability. Another study used the handy probe to test the effect of the palatal plate on swallowing pressure [23]. Although perceived difficulty in swallowing increased by wearing palatal plate, tongue strength and swallowing pressure were not influenced in healthy dentate subjects.…”
Section: Handy Probementioning
confidence: 99%